Microbiological analysis of fish feed - Belichovska Katerina, Belichovska Daniela, Gjorgjievski Srekjko (MIT University, Skopje, 2016)
The microbiological fish feed analysis for commercial fish was performed in two fish ponds. The feed originated from Greece, Italy and the Netherlands. The microbiological tests were performed during the months of March, May, July, August, September and October. From the feed analysis it can be concluded that two samples of fish feed mixtures from May and July, in the first fish pond, and one sample of feed from August, in the second fish pond showed the presence of pathogenic microorganisms, respectively only three fish feed mixtures were not appropriate for fish feeding.
Keywords: fish feed, microbiological analysis